2011
DOI: 10.1590/s1413-78522011000300008
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do ganho funcional do cotovelo com a cirurgia de Steindler na lesão do plexo braquial

Abstract: Objective: To evaluate the gain in strength and range of motion after modified Steindler surgery of the elbow in patients with lesions of the upper trunk of the brachial plexus. Method: From 1998 to 2007, eleven patients with traumatic closed upper trunk lesion of the brachial plexus were studied. All the patients had development of at least 1 year of injury and degree of strength of elbow flexion ranging from M1 to M3. The patients underwent Steindler surgery with at least 6 months of follow-up. Pre-and post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…In performing this technique, this musculature is made to act as an elbow flexor. Our experience with this procedure confirms other authors' experience (53) that indicated that this transfer is efficient for boosting elbow flexion, i.e., when the existing elbow flexor musculature is at least grade 2 (54). This transfer has been shown to be insufficient for achieving functional elbow flexion on its own.…”
Section: Diagnostic Methodssupporting
confidence: 87%
“…In performing this technique, this musculature is made to act as an elbow flexor. Our experience with this procedure confirms other authors' experience (53) that indicated that this transfer is efficient for boosting elbow flexion, i.e., when the existing elbow flexor musculature is at least grade 2 (54). This transfer has been shown to be insufficient for achieving functional elbow flexion on its own.…”
Section: Diagnostic Methodssupporting
confidence: 87%
“…Of the 18 patients who underwent functional evaluation, seven (38.89%) were not able to dissociate the flexion movement of the elbow from the flexion movements of the wrist and fingers (Group 1) and 11 (61.11%) were able to dissociate these movements (Group 2) 15 . Five patients from Group 1 and five from Group 2 presented injury at C5, C6, and C7.…”
Section: Resultsmentioning
confidence: 99%